Franco : - Crozier, Brian (Eyre & Spottiswoode, 1967)
DJ is only GOOD with edgeware and shelfware but no real damage. Black marker line on pg bottoms. Well Researched with the consent of the Spanish authorities even thought they knew it would not be flattering. No International or Priority.